The Effect of Flipped Learning Model on EFL Learners' Academic Achievement, Self-Esteem and Self-Confidence - Hojjat Namdaran; Omid Akbari (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
The aim of the study is to examine the effect of flipped learning model on EFL learners academic achievement, self-esteem and self-confidence. This is a quantitative qualitative study in which a mixed methods design is used for data collection procedure. The study sample includes two groups of intermediate English students who study in foreign language institutions. They are selected by purposive sampling method. This method of sampling allows the researcher to select students with two years of learning experience. In this study, the independent variable of the research is flipped learning model, as opposed to traditional learning approach, while the dependent variables are students academic achievement, self-esteem, and self-confidence. One sample pre-test and post-test design is used to collect quantitative data on academic achievement, self-esteem and self-confidence. In order to collect qualitative data, a semi-structured interview is administered to reveal the general attitudes of the students towards the benefits, difficulties and the solutions of the flipped classroom. The results indicate that flipped learning model has significant effect on EFL learners academic achievement, self-esteem and self-confidence. The researcher concludes that learners with high self-confidence and self-esteem will have a greater academic achievement, and flipped classroom can enhance language learning.